Self-initiated versus externally triggered movements. I. An investigation using measurement of regional cerebral blood flow with PET and movement-related potentials in normal and Parkinson's disease subjects. - Jahanshahi, M; Jenkins, I; Brown, R; Marsden, C; Passingham, R; Brooks, D (1995)
We investigated the functional anatomy of self-initiated and externally triggered movements. Six patients with Parkinson's disease off medication and six age-matched normals were assessed. All subjects had regional cerebral blood flow (rCBF) measurement with PET and recording of movement-related cortical potentials (MRPs) from frontal (F), fronto-central (FC), central (C) and parietal (P) sites to obtain measures of the Bereitschaftspotential (BP). The tasks were (i) self-initiated extension of the right index finger on average once every 3 s, (ii) externally triggered finger extension with the rate yoked to the self-initiated task, and (iii) rest condition with tones presented at a rate yoked with the self-initiated task. For the self-initiated movements, the amplitude of the early and peak BP were lower in Parkinson's disease relative to normals. For the externally triggered movements, the patients and the normals did not differ on any of the measures of cortical negativity prior to movement. For both groups, the late and peak BP components, but not the early component, had a lower amplitude in the externally triggered than the self-initiated movements. In normals, the left primary sensorimotor cortex, the supplementary motor area bilaterally, anterior cingulate, the lateral premotor cortex bilaterally, the insular cortex bilaterally, the left thalamus and the left putamen, parietal area 40 bilaterally and the right dorsolateral prefrontal cortex (DLPFC) were significantly activated during the self-initiated movements relative to rest. For the normals, greater activation of the right DLPFC during the self-initiated movements was the only area that significantly differentiated them from the externally triggered movements. When Parkinson's disease patients and normals were compared for the self-initiated movements relative to rest, normals showed greater activation of the supplementary motor area and anterior cingulate, left putamen, left insular cortex, right DLPFC and right parietal area 40. When the groups were compared for the externally triggered movements relative to rest, the global pattern of blood flow and rCBF change in the two groups did not differ, confirming the absence of group differences in BPs for the externally triggered movements. During the self-initiated movements, the lower amplitude of the early BP in patients with Parkinson's disease as well as the underactivation of the supplementary motor area relative to normals support the premises that (i) the supplementary motor area contributes to the early BP, and (ii) the deficit is self-initiated movements in Parkinson's disease is due to supplementary motor area underactivation. The DLPFC is activated in situations requiring non-routine decision making as in the self-initiated movements.